1979
DOI: 10.1080/02541858.1979.11447670
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption and responses of the freshwater snailBulinus(Physopsis) globosus to gradients of different oxygen tensions

Abstract: A gradient or choice apparatus, based on the 'fluvarium' principle and suitable for testing the responses of the freshwater snail Bulinus (Physopsis) globosus to different partial oxygen tensions was used. In a gradual oxygen gradient established with this apparatus, B. (P.) globosus shows a significant preference for oxygenated water. In experiments with a choice between low and high partial oxygen tensions, B. (P.) globosus shows a greater preference for oxygenated water. Oxygen consumption rates vary consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…1) and houses the oxygen electrode. The cell has two 3 mm diameter ports (Van Aardt and Frey, 1979).…”
Section: The Po 2 Measuring Cellmentioning
confidence: 99%
“…1) and houses the oxygen electrode. The cell has two 3 mm diameter ports (Van Aardt and Frey, 1979).…”
Section: The Po 2 Measuring Cellmentioning
confidence: 99%
“…This highly vascularized secondary gill (Van Aardt & Van Eeden 1969; Baker 1945) evolved when planorbids from a divergent stock of land pulmonates established themselves in temporary freshwater bodies low in oxygen content (Baker 1945). Furthermore it was found (Van Aardt & Frey 1979) that the oxygen depletion rate of a body of water by B. africanus is linear against time up to a partial oxygen pressure of 42 mmHg at 26°C. This P0 2 value, the critical oxygen pressure, Pc, (Herreid 1980) is usually determined by the limitations of the oxygen-carrying capacities of the haemolymph, particularly the haemoglobin part (McMahon 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known of the tolerance of low dissolved oxygen levels by B. pfeifferi, Jones (1964), Smith (1982) and Van Aardt & Frey (1979) have shown that various species of Biomphalaria and Bulinus can withstand very low oxygen tensions. This is possible because the haemoglobin of these aquatic planorbids has an extremely high affinity for oxygen.…”
Section: Discussionmentioning
confidence: 99%